Small Brands, Big Impact": Harnessing the Long Tail for Market Success - Ratna Deli, Sari (INTI International University, 2025)
This book provides an overview of the significant changes in the marketing landscape driven by the advancement of digital technology and shifts in consumer behavior, particularly with the emergence of Generation Z, who prefer unique and personalized products. It also explores how marketing strategies have shifted towards targeting highly specific market segments (niches) that can leverage digital platforms like e-commerce and social media. The goal of this book is to highlight how small businesses and MSMEs, previously constrained by traditional, costly marketing methods and physical distribution challenges, can now compete effectively in a global market using digital tools. These tools enable affordable content marketing, distribution via marketplaces, and the use of algorithms that help discover niche products. Ultimately, this book contends that this change presents significant new opportunities for smaller brands to not only survive but to thrive in an increasingly fragmented market. By focusing on changes in the marketing mix—product, price, distribution, and promotion—it offers valuable insights into how marketing has evolved and what MSMEs must do to succeed in this new era.